2016
DOI: 10.1016/j.cell.2015.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Clusters into Lipid Microdomains on Phagosomes to Drive Rapid Transport toward Lysosomes

Abstract: SummaryDiverse cellular processes are driven by motor proteins that are recruited to and generate force on lipid membranes. Surprisingly little is known about how membranes control the force from motors and how this may impact specific cellular functions. Here, we show that dynein motors physically cluster into microdomains on the membrane of a phagosome as it matures inside cells. Such geometrical reorganization allows many dyneins within a cluster to generate cooperative force on a single microtubule. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
311
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(330 citation statements)
references
References 46 publications
17
311
2
Order By: Relevance
“…Conceivably then, reggies might organize microdomains with specific lipids and lipid modified proteins and promote their vesicular transport and delivery to specific regions such as the PSD. This complies with a recent report showing that dynein clusters in reggie/flotillin microdomains during transport and maturation of phagosomes to lysosomes in Leishmania donovani (Rai et al, 2016).…”
Section: Reggies In Raftssupporting
confidence: 79%
“…Conceivably then, reggies might organize microdomains with specific lipids and lipid modified proteins and promote their vesicular transport and delivery to specific regions such as the PSD. This complies with a recent report showing that dynein clusters in reggie/flotillin microdomains during transport and maturation of phagosomes to lysosomes in Leishmania donovani (Rai et al, 2016).…”
Section: Reggies In Raftssupporting
confidence: 79%
“…Nelson et al [63] demonstrated that the fluidity of the bilayer affects the velocity of myosin teams synthetically anchored to phospholipid vesicles. On the other hand, dyneins cluster into raft-like microdomains on phagosomes improving their performance as a team [72]. These previous works show that the cargo membrane plays a relevant role on the performance of motor teams.…”
Section: Resultsmentioning
confidence: 99%
“…This results in less slippage of the motors and thus an increased transport efficiency. Along these lines, a recent study has reported that cytoplasmic dynein clusters into lipid microdomains on phagosomes to drive rapid transport toward lysosomes (41).…”
Section: Discussionmentioning
confidence: 99%